2024
DOI: 10.1186/s12864-024-10038-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel diabetic foot ulcer diagnostic model: identification and analysis of genes related to glutamine metabolism and immune infiltration

Hongshuo Shi,
Xin Yuan,
Xiao Yang
et al.

Abstract: Background Diabetic foot ulcer (DFU) is one of the most common and severe complications of diabetes, with vascular changes, neuropathy, and infections being the primary pathological mechanisms. Glutamine (Gln) metabolism has been found to play a crucial role in diabetes complications. This study aims to identify and validate potential Gln metabolism biomarkers associated with DFU through bioinformatics and machine learning analysis. Methods We down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Wound healing is a regulated and highly complex biological process. It is reported that immune/inflammatory regulation is crucial in the wound healing process [ 57 ]. To investigate the role of immune/inflammatory cells in DFU wound deterioration, we performed a comprehensive assessment of the immune microenvironment of DFUs and presented different cellular components in the immune microenvironment between DFUs and Controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound healing is a regulated and highly complex biological process. It is reported that immune/inflammatory regulation is crucial in the wound healing process [ 57 ]. To investigate the role of immune/inflammatory cells in DFU wound deterioration, we performed a comprehensive assessment of the immune microenvironment of DFUs and presented different cellular components in the immune microenvironment between DFUs and Controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that macrophages play a role in hemostasis and that pro-inflammatory macrophages infiltrate and remove dead cells and bacteria from the wound site after injury [ 60 ]. During the wound healing phase, macrophage polarization stimulates the movement and growth of fibroblasts, endothelial cells, and keratinocytes, which accelerates repair of the epidermis, dermis, and vascular system [ 57 ]. Additionally, it has been shown that decreased innate immunoregulatory function exacerbates macrophage polarization imbalance as well as decreased wound healing [ 61 ], which is also consistent with the results of the immune infiltration analyses mentioned above, suggesting that a significant down-regulation of the abundance of dominant immune cells in DFUs, including B and T cells, leads to a decrease in wound healing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery, validated through external datasets and immunohistochemistry, underscores GSTM5’s potential influence on essential signaling pathways and its association with T cells, paving the way for targeted immune therapies ( 61 ). Equally important is that another pivotal study sheds light on glutamine metabolism’s role in DFU pathogenesis ( 62 ). By analyzing microarray datasets from the GEO database, this research unveiled differential expressions of glutamine metabolism-related genes and their correlation with immune cell infiltration in DFU patients.…”
Section: Advancements In Diabetic Foot Care: Exploring Machine Learni...mentioning
confidence: 99%
“…By analyzing microarray datasets from the GEO database, this research unveiled differential expressions of glutamine metabolism-related genes and their correlation with immune cell infiltration in DFU patients. The employment of a SVM model, based on 5 critical genes, demonstrated remarkable predictive accuracy (AUC = 0.929) on external validation datasets ( 62 ). Furthermore, investigations into angiogenesis-related genes using machine learning algorithms underscored the vital function of angiogenesis in DFU’s wound healing process ( 63 ).…”
Section: Advancements In Diabetic Foot Care: Exploring Machine Learni...mentioning
confidence: 99%
See 1 more Smart Citation